Activation of the olefinic C-H bond of NHC and NHO by perimidine-based silicon and germanium compounds - Gour, Kritika; Pramanik, Debjit; Dash, Soumya Ranjan; Tothadi, Srinu; Vanka, Kumar; Sen, Sakya S. (Organometallics, 2023)
In this manuscript, several backbonegermylene-functionalized zwitterioniccompounds were prepared conveniently from the corresponding N-heterocycliccarbenes or N-heterocyclic olefins in a single step through backboneC-H activation. Our initial motivation was to generate a silylenefrom C10H6(Me3SiN)(2)SiHCl(2) using ItBu [ItBu= (1,3-ditert-butyl)imidazol-2-ylidene], but instead, the reactionled to deprotonation from the imidazolium backbone of ItBu, forming the imidazolium salt with a silyl backbone at the C4position (3). We presumed that the reaction proceededthrough the generation of an ephemeral silylene. We subsequently preparedthe analogous germylene (4) and reacted it with IDipp[IDipp = 1,3-bis(2,6-diisopropylphenyl)imidazol-2-ylidene], ItBu, and IDipp=CH2. Spectroscopic and crystallographicanalysis of these complexes revealed that, in all cases, there wasdeprotonation from the backbone and formation of zwitterionic products(5-7). When the hydrogen in the NHCbackbone was replaced with methyl groups such as IDipp(Me) (1,3-bis(2,6-diisopropylphenyl)-4,5-dimethylimidazol-2-ylidene),simple adduct formation occurred, exemplified by the isolation ofIDipp(Me)& BULL;Ge(NSiMe3)(2)C10H6 (8).